Adsorption and Inhibition Analysis of Aconitine and Tubocurarine Alkaloids as Eco-friendly Inhibitors of Pitting Corrosion in ASTM – A47 Low Carbon Steel in HCl Acid Environment - Benedict Ushaka Ugi; Mbang Eze Obeten; Victoria Mfon Bassey; Louis Hitler; Stephen Adie Adalikwu; Chijioke Everistus Omaliko; Desmond Obi Nandi; Ikama Edet Uwah (Indonesian Journal of Chemistry, 2022)
Corrosion is an enormous challenge in all sectors of the economy, especially to those working with metals. The research on the adsorption and inhibition analysis of aconitine alkaloid (ACA) and tubocurarine alkaloid (TBA) as eco-friendly inhibitors of pitting corrosion in ASTM – A47 low carbon steel in HCl acid was carried out under the following experimental methods: gravimetric method, gasometric method, electrochemical impedance spectroscopy, potentiodynamic polarization, and scanning electron microscopy. Results revealed good inhibitors as inhibition efficiencies were recorded at 98.8% and 91.2% at a maximum inhibitor concentration of 1500 ppm for tubocurarine and aconitine alkaloids, respectively. The inhibition efficiency was found to increase with increasing inhibitor concentrations indicating a strong binding between inhibitor molecules and ASTM – A47 low carbon steel in HCl acid. Electrochemical data strongly supported the efficacy of both inhibitors as earlier presented by the chemical methods as a trend in values of charge transfer resistance, double layer capacitance, corrosion potential, and corrosion current density were in accordance with standards for a good inhibitor. The inhibitors were seen to be spontaneous, stabled, endothermic and physically adsorbed. Adsorption of the inhibitors on metal surface obeyed Langmuir, El-Awady, Freundlich, and Temkin adsorption isotherm as regression values were approximately unity.